Ehrlichia and Anaplasma Infections: Serological Evidence and Tick Surveillance in Peninsular Malaysia - Koh, Fui Xian; Kho, Kai Ling; Kisomi, Masoumeh Ghane; Wong, Li Ping; Bulgiba, Awang; Tan, Poai Ean; Lim, Yvonne Ai Lian; Nizam, Quaza Nizamuddin Hassan; Panchadcharam, Chandrawathani; Tay, Sun Tee (Oxford University Press, 2017)
Little information is available on human anaplasmosis and ehrlichiosis in Southeast Asia despite increasing reports of the detection of Anaplasma spp. and Ehrlichia spp. in the ticks. We report herein the serological findings against the tick-borne pathogens in a group of animal farm workers (n = 87) and indigenous people (n = 102) in Peninsular Malaysia. IgG antibodies against Ehrlichia chaffeensis were detected from 29.9% and 34.3% of farm workers and indigenous people, respectively, using commercial indirect immunofluorescence assays. Comparatively, only 6.9% of the indigenous people but none of the animal farm workers were seropositive to Anaplasma phagocytophilum. A polymerase chain reaction (PCR) assay targeting the 16S rRNA gene of Anaplasmataceae was used to identify Anaplastamataceae in ticks collected from various locations adjacent to the areas where the serological survey was conducted. In this study, a total of 61.5% of ticks infesting farm animals, 37.5% of ticks infesting peri-domestic animals in rural villages, 27.3% of ticks collected from wildlife animals, and 29.1% of questing ticks collected from forest vegetation were positive for Anaplasmataceae DNA. Sequence analyses of 16S rRNA gene region (238 bp) provide the identification for Anaplasma marginale, Anaplasma bovis, Anaplasma platys, A. phagocytophilum, and Anaplasma spp. closely related to Candidatus Cryptoplasma californiense in ticks. E. chaffeensis DNA was not detected from any ticks, instead, Ehrlichia sp. strain EBm52, Ehrlichia mineirensis and Candidatus Ehrlichia shimanensis are the only Ehrlichia sp. identified from cattle ticks in this study. Further investigation is required to ascertain the occurrence of zoonotic transmission of Ehrlichia and Anaplasma infections in Peninsular Malaysia.